Respuesta :

Answer:

- 8

Step-by-step explanation:

Evaluate f(1) and f(- 1) by substituting x = 1 and x = - 1 into f(x)

Given

f(x) = x² - 4x + 6, then

f(1) = 1² - 4(1) + 6 = 1 - 4 + 6 = 3

f(- 1) = (- 1)² - 4(- 1) + 6 = 1 + 4 + 6 = 11

Thus

f(1) - f(- 1) = 3 - 11 = - 8

Answer:

[tex]The~ value ~of~ f(1) - f(-1)~ is~ -8.[/tex]

Step-by-step explanation:

[tex]The~given~function:[/tex]

[tex]f(x)=x^2-4x+6[/tex]

[tex]We~ need~ to~ find~ the~ value ~of ~f(1) - f(-1).[/tex]

[tex]Substitute~ x=1~ in~ the~ given~ function.[/tex]

[tex]f(1)=(1)^2-4(1)+6=3[/tex]

[tex]Substitute~ x=-1~ in~ the~ given ~function .[/tex]

[tex]f(-1)=(-1)^2-4(-1)+6=11[/tex]

[tex]The~ of ~f(1) - f(-1)~ is[/tex]

[tex]f(1)-f(-1)=3-11=-8[/tex]

Therefore, the value of f(1) - f(-1) is -8.